Comparative study of the calculated risk of radiation-induced cancer after photon- and proton-beam based radiosurgery of liver metastases. (October 2017) - Mondlane, Gracinda; Gubanski, Michael; Lind, Pehr A.; Ureba, Ana; Siegbahn, Albert
Highlights: Comparison of risks for cancer induction after SBRT and IMPT of liver metastases. With the Dasu-model, the highest risks were estimated for the skin. With the Schneider-model, the highest risk-ratios were estimated for the liver. Both the fatal- and total-cancer risks were lower when the IMPT method was used. Both the carcinoma- and sarcoma risks were lower when the IMPT method was used. Abstract: Introduction: The potential of proton therapy to improve the sparing of the healthy tissue has been demonstrated in several studies. However, even small doses delivered to the organs at risk (OAR) may induce long-term detriments after radiotherapy. In this study, we investigated the possibility to reduce the risk of radiation-induced secondary cancers with intensity modulated proton therapy (IMPT), when used for radiosurgery of liver metastases. Material and methods: Ten patients, previously treated for liver metastases with photon-beam based stereotactic body radiation therapy (SBRT) were retrospectively planned for radiosurgery with IMPT. A treatment plan comparison was then performed in terms of calculated risk of radiation-induced secondary cancer. The risks were estimated using two distinct models (Dasu et al., 2005; Schneider et al., 2005, 2009). The plans were compared pairwise with a two-sided Wilcoxon signed-rank test with a significance level of 0.05. Results: Reduced risks for induction of fatal and other types of cancers were estimated for the IMPT plans (p < 0.05) with the Dasu et al. model. Using the Schneider et al. model, lower risks for carcinoma-induction with IMPT were estimated for the skin, lungs, healthy part of the liver, esophagus and the remaining part of the body (p < 0.05). The risk of observing sarcomas in the bone was also reduced with IMPT (p < 0.05). Conclusion: The findings of this study indicate that the risks of radiation-induced secondary cancers after radiosurgery of liver metastases may be reduced, if IMPT is used instead of photon-beam based SBRT.